Identifikasi Telur Cacing Nematoda Usus Pada Feses Anak Usia 5-10 Tahun - Fitriani Kahar; Quirinus Efendi; Ichsan Hadipranoto (Poltekkes Kemenkes Semarang, 2020)
Humans are the host of several intestinal nematodes, most of which can cause public health problems. Among intestinal nematodes there are species that are transmitted through soil or called